تصميم المجرى الحلزوني لريشة الثقب بوساطة الحاسوب - الحموي لطيفة عبد الحفيظ (Latakia University Journal -Engineering Sciences Series, 2019)
يعطي البحث فكرة هامة عن تصميم المجرى الحلزوني لريشة الثقب برمجياً تبعاً للمقادير الهندسية الخاصة بهذا المجرى. تم استخدام وبرمجة نظرية الأقواس للحصول على النتائج النظرية والعملية مع اعتبار تأثير زاوية الجرف على عمل مجرى الريشة الحلزوني. ولقد تبين من خلال البحث أن النتائج التي تم الحصول عليها تتوافق مع الأفكار النظرية والعملية المقترحة سابقاً. The present work gives an important idea about a programmed helical flute cutting drill tool design, with its special geometry parameters. The ares method is used and programmed to achieve the theoretical and experimental results, since the rake angle influences the helical drill work. The results obtained are in agreement with the theoretical and experimental ideas previously proposed.